Contemporary Fragments in Islamic Interpretation: An Analysis of Gus Baha's Tafsir Jalalayn Recitation on YouTube in the Pesantren Tradition - Mahfidhatul Khasanah Khasanah; Saifuddin Zuhri Qudsy; Thoriqatul Faizah (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2023)
The impact of digital technology on Indonesian society has been profound, leading to changes in cultural and religious practices. This study focuses on the phenomenon of Gus Baha's Jalalayn Tafsir recitation on YouTube and aims to understand how this has become a contemporary fragment in the history of tafsir recitation in Indonesian pesantrens. The study employs a media theory approach popularized by Marshall McLuhan to analyze the workings and impact of this recent phenomenon. McLuhan's theory includes three main ideas, such as Medium is The Message and Medium as Extension of Man, which are used to explore the new workings of Gus Baha's Jalalayn Tafsir recitation on YouTube, as well as the Global Village and Technology Determinism to understand the impact of this phenomenon. The study seeks to answer two key questions: (1) how is the phenomenon of Gus Baha's Tafsir recitation on YouTube and (2) how it has become part of the long history of pesantren tradition. The results of this study will provide insights into how digital technology has changed religious practices in Indonesia and the role of YouTube in this change.